Exploring fatigue sensitivity in terms of mental health and fatigue severity among a racially and ethnically diverse sample with severe fatigue. Issue 3 (3rd July 2022) - Manning, Kara; Mayorga, Nubia A.; Nizio, Pamella; Heggeness, Luke F.; Kauffman, Brooke Y.; Garey, Lorra; Zvolensky, Michael J.
ABSTRACT: Background: Fatigue sensitivity, or the misattribution that fatigue symptoms will lead to negative personal consequences, is one individual difference factor related to adverse behavioral health consequences. Methods: The current study investigated whether fatigue sensitivity was related to panic symptoms, depression, as well as fatigue severity among 166 persons of diverse racial/ethnic backgrounds with severe fatigue. Results: As hypothesized, fatigue sensitivity was statistically significantly related to greater panic symptoms, general depression, and fatigue severity. These results were evident over the variance explained by age, sex, neuroticism, and somatic symptoms. Conclusions: This work is the first to evaluate fatigue sensitivity in terms of behavioral health outcomes among a racial/ethnically diverse sample with severe fatigue.